2020
DOI: 10.1017/dmp.2020.255
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Recommendations for the Use of Dental Masks in the Prevention of COVID-19: A Literature Review

Abstract: The purpose of this investigation was to identify, synthesize and compare all the current information on the efficacy of dental masks, emphasizing their use, types and filters to prevent the spread and infection of COVID-19 and other infectious diseases. A bibliographic search of the main scientific databases was carried out using the words “masks, COVID-19 and dentistry”. Articles without language restriction up to May 31, 2020 were obtained. The types of masks, their half-life, method to use, sterilization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
(103 reference statements)
1
33
1
1
Order By: Relevance
“…When assessing the implementation of national and international COVID-19 guidelines for dental practice, we found that 97.83% of the surveyed dental offices implemented protective equipment for doctors [ 28 ] (PPE), 82.05% patient triage, 89.74% proper time gaps between patients, and 95.66% patient temperature checks. In line with international literature, this study also provides evidence for the effectiveness of PPE as an essential regulation for preventing the spread of the virus to and from healthcare providers and patients [ 29 , 30 , 31 ]. Enhanced protective equipment for dental practitioners, patient phone triage, allowing regular time gaps between patients are thus considered to be more efficient than gloves, caps, and robes for patients.…”
Section: Discussionsupporting
confidence: 70%
“…When assessing the implementation of national and international COVID-19 guidelines for dental practice, we found that 97.83% of the surveyed dental offices implemented protective equipment for doctors [ 28 ] (PPE), 82.05% patient triage, 89.74% proper time gaps between patients, and 95.66% patient temperature checks. In line with international literature, this study also provides evidence for the effectiveness of PPE as an essential regulation for preventing the spread of the virus to and from healthcare providers and patients [ 29 , 30 , 31 ]. Enhanced protective equipment for dental practitioners, patient phone triage, allowing regular time gaps between patients are thus considered to be more efficient than gloves, caps, and robes for patients.…”
Section: Discussionsupporting
confidence: 70%
“…Effective use of PPE, including, gowns, gloves, face shields, goggles, and face masks, is an essential regulation for preventing the spread of the virus to and from healthcare providers and patients [33,34]. While the rapid enhance of demand for PPE resulted in the shortage of these supplies all around the world [35].…”
Section: Discussionmentioning
confidence: 99%
“…Effective use of PPE, including, gowns, gloves, face shields, goggles, and face masks, is an essential regulation for preventing the spread of the virus to and from health-care providers and patients (34,35). While the rapid enhance of demand for PPE resulted in the shortage of these supplies all around the world (36).…”
Section: Discussionmentioning
confidence: 99%